Mothers as Clients of Family Preservation Services: A Socio-demographic and Development Profile - Menéndez Álvarez-Dardet, Susana; Arenas Roja, Ángela Victoria; Pérez Padilla, Javier; Lorence Lara, Bárbara (Cuadernos de Trabajo Social, 2012)
At-risk families are a central group within the Social and Community Services client population and, in recent years, there is ongoing research in our country about them. In this article, we present results obtained from a survey of a sample of mothers who receive family preservation services from Social and Community Services of the Province of Huelva. Specifically, their socio-demographic and economic profile, their degree of poverty in relation to the official poverty line and their case history and current situation in Social Services while exploring the professional assessments made regarding the evolution of these families are presented. Differences in the areas analyzed according to the type of service are also examined.